Delayed Ovulation in Bovine: Diagnosis and Treatment - H., Al-Timimi I.; J., Khammas D.; M., Al-Hamedawi T. (The Iraqi Journal of Veterinary Medicine, 2021)
Repeated breeder dairy cows (96) were used in this study. They were diagnosed clinically as cases of delayed ovulation and divided into five groups according to type of treatment used post insemination. Group one which includes 28 cow (1=28) treated with 1 vial of fertagyl, (2=22) treated with 2 vials of fertagyl, (3=19) treated with 5 ml of chorionic gonadotropin, (4=17) treated with 1 vial of Nymfalom and (5=10) treated with 1 vial of chorulon. Results showed that the number of cows which did not return to estrus (responded) were 16(57.14%), 12(54.54%), 9(47.47%), 12(70.6%) and 4(40%) respectively. Treatment and insemination were repeated to a number of unresponded cows and their results revealed response of 3 cows (27.27%) from group (1=11), response of 4 cows (50%) from group (2=8), response of 3 cows (42.85%) from group (3=7), response of 1 cow (20%) from group (4=5) and response of 2 (50%) from group (5=4). Data concerning the number, type, sex and viability of the offspring born from the treated cows were included in this study. Finally we may conclude that Nymfalon showed better result in treating cases of delayed ovulation and in improving their conception and pregnancy rate. The remaining treatments were also advisable in the absence of Nymfalon. The use of the same treatment again was also beneficial in some unresponded cases.